Dose-Finding Methodology for Peripheral Nerve Blocks. Issue 6 (1st November 2014) - Saranteas, Theodosios; Finlayson, Roderick J.; Tran, De Q. H.
Abstract : Abstract: Dose-finding studies enable the successful conduct of peripheral nerve blocks by ensuring the administration of appropriate doses of local anesthetic. However, the optimal dose-finding methodology remains ambiguous. In this research methodology article, we set out to review the basic aspects pertaining to dose-response curves (graded vs quantal), the pharmacodynamic indices required by dose-finding studies, the properties of different dose-finding methods (sigmoidal dose-response curve analysis, Dixon-Mood method, Biased Coin Design, and Bayesian analysis), as well as strategies and recommendations for future research.